The Principal's Leadership Role in Driving Educational Innovation: Strategies and Challenges - Alin Natul Muslihah; Sulis Binti Munfaati; Rizeki Munatul Fadhilah; Tamrin Fathoni; Rusli Wan (Tamilis Synex: Multidimensional Collaboration, 2024)
Educational innovation has become a strategic necessity for schools in responding to rapid technological developments, curriculum reforms, and the changing demands of 21st-century learning. The principal plays a pivotal role as an instructional leader, change agent, and strategic decision-maker in fostering innovative educational practices. This study examines the principal’s leadership role in driving educational innovation, focusing on the strategies employed and the challenges encountered during implementation. Through a review of contemporary educational leadership literature, the study identifies key leadership strategies, including the development of a shared vision, promotion of teacher professional development, integration of educational technology, encouragement of collaborative cultures, and support for continuous improvement initiatives. The study also highlights several challenges, such as resistance to change, limited financial resources, inadequate technological infrastructure, and varying levels of teacher readiness. Findings indicate that effective leadership significantly influences the successful adoption and sustainability of innovation in schools. Principals who demonstrate transformational and adaptive leadership are better positioned to overcome barriers and create environments conducive to innovation. The study underscores the importance of leadership capacity-building to ensure continuous educational improvement and institutional effectiveness.